Correction: X-ray pair distribution function analysis and electrical and electrochemical properties of cerium doped Li5La3Nb2O12 garnet solid-state electrolyte. Issue 35 (26th August 2020) - Dong, Bo; Stockham, Mark P.; Chater, Philip A.; Slater, Peter R.
Abstract : Correction for 'X-ray pair distribution function analysis and electrical and electrochemical properties of cerium doped Li5 La3 Nb2 O12 garnet solid-state electrolyte' by Bo Dong et al., Dalton Trans., 2020, 49, 11727–11735, DOI: ; 10.1039/d0dt02112a .